2016
DOI: 10.1242/dev.145870
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin regulates sorting and secretion of Sonic hedgehog

Abstract: Sonic Hedgehog (Shh) is a secreted morphogen that is an essential regulatorof patterning and growth. The Shh full-length protein undergoes autocleavage in the endoplasmic reticulum to generate the biologically active N-terminal fragment (ShhN), which is destined for secretion. We identified sortilin (Sort1), a member of the VPS10P-domain receptor family, as a new Shh trafficking receptor. We demonstrate that Sort-Shh interact by performing coimmunoprecipitation and proximity ligation assays in transfected cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…1 C). HhU self-cleavage to yield HhNp and HhC 24 is thought to occur in the ER ( Campbell et al, 2016 ; Chen et al, 2011 ). To determine how HhC 24 and HhC 16 are processed, we employed Hh-expressing cell lines which enabled us to observe the generation and degradation order of Hh products, the secretion of each fragment, and the organellar compartments in which these events occur.…”
Section: Resultsmentioning
confidence: 99%
“…1 C). HhU self-cleavage to yield HhNp and HhC 24 is thought to occur in the ER ( Campbell et al, 2016 ; Chen et al, 2011 ). To determine how HhC 24 and HhC 16 are processed, we employed Hh-expressing cell lines which enabled us to observe the generation and degradation order of Hh products, the secretion of each fragment, and the organellar compartments in which these events occur.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the effect of sortilin on NT function, reports have established that sortilin interacts with other known molecules of relevance for neural development. Most notably, a recent report found that sortilin is a regulator of sonic hedgehog secretion, a protein with profound impact on CNS patterning and development (Campbell et al, ). Sortilin enhances signaling of ciliary neurotrophic factor (CNTF), shown to mediate survival of several neuronal subtypes (Larsen et al, ; Sango, Yanagisawa, Komuta, Si, & Kawano, ) and decreases levels of progranulin, a protein involved in the pathogenesis of frontotemporal lobar dementia (Baker et al, ; Hu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that impaired phosphorylation of Y1062 in c-Ret causes impairments of neurite outgrowth and SV2-mediated Shh trafficking in PCs, resulting in hypoplasia of GCs and glial fibers with decreased expression of BLBP. In a previous study, Sortilin, a multifunctional sorting receptor, was shown to regulate Shh trafficking (41). Therefore, it is possible that Shh trafficking is mediated by not only SV2-mediated processes but also other processes.…”
Section: Discussionmentioning
confidence: 98%